DNA-Stable Isotope Probing Shotgun Metagenomics Reveals the Resilience of Active Microbial Communities to Biochar Amendment in Oxisol Soil - Yu, Julian; Pavia, Michael J.; Deem, Lauren M.; Crow, Susan E.; Deenik, Jonathan L.; Penton, Christopher Ryan (Frontiers in Microbiology, 2020)
The dynamics of individual microbial populations and their gene functions in agricultural soils amended with biochar remain elusive but are important for a deeper understanding of nutrient cycling and carbon (C) sequestration. In this study, we coupled DNA stable isotope probing (SIP) with shotgun metagenomics in order to target the active community in microcosms which contained soil collected from biochar-amended and control plots under napiergrass cultivation. Our analyses revealed that the active community was composed of high-abundant and low-abundant populations, including Actinobacteria, Proteobacteria, Gemmatimonadetes, and Acidobacteria. Although biochar did not significantly shift the active taxonomic and functional communities, we found that the narG (nitrate reductase) gene was significantly more abundant in the control metagenomes. Interestingly, putative denitrifier genomes generally encoded one gene or a partial denitrification pathway, suggesting denitrification is typically carried out by a collection of different populations within this Oxisol soil. Altogether, these findings indicate that the impact of biochar on the active soil microbial community are transient in nature. As such, the addition of biochar to soils appears to be a promising strategy for the long-term C sequestration in agricultural soils, does not impart lasting effects on the microbial functional community, and thus mitigates un-intended microbial community shifts that may lead to fertilizer loss through increased N cycling.